Incorporating the non-separable characteristic of undesirable outputs into congestion analysis: a case of regional industries in China. (19th May 2019) - Cho, Cheng-Chung; Yang, Fu-Chiang
ABSTRACT: Congestion is a widely observed economic phenomenon, where excessive amounts of the input cause a reduction of the output. Recently, incorporating undesirable outputs (such as pollutants or wastes) into congestion analysis along with desirable outputs is an emerging issue in data envelopment analysis studies. However, existing methods of congestion measurement do not overall consider the non-separable characteristic of undesirable outputs, where a reduction of undesirable outputs is accompanied by a proportionate reduction in not only desirable outputs but also inputs. Based on the slacks-based measure approach, this paper develops a new method for congestion analysis that keeps a close link between undesirable outputs, desirable outputs, and inputs. The presented method is applied to a case study of 31 administrative regions of China for investigating resource utilization and environmental problems. Lastly, this study summarizes the comparisons of the proposed and existing methods.